Comparative study between onlay and sublay repair of ventral hernia - Radwa M Mohamed; Omnia M Rabie (Wolters Kluwer Medknow Publications, 2019)
Background Ventral hernia is one of the most common surgical operations performed all over the world. Surgical repair is done using prolene mesh and can be placed over anterior rectus sheath (onlay) or in preperitoneal space. However, the debate still continues about the superiority of each technique over the other. Aim To study operative time, easy of procedure, early postoperative complications, duration of hospital stays, recurrences, and outcomes of the onlay versus sublay mesh repair. Patients and methods One hundred patients with paraumbilical, epigastric, and supraumbilical incisional hernias were included in this study and were managed at Al Zahra Hospital. Patients were divided into two main groups: group A underwent onlay mesh repair and group B sublay mesh repair. The patients included were evaluated for operating time, postoperative seroma formation wound infection, drain duration, postoperative hospital stay, and recurrence of symptoms. Results A total of 100 patients were operated in our study: 50 patients were in group A and 50 patients in group B. The mean operative time in group B was 70±18.50 min and in group A was 50±12. The duration of hospital stay was on an average 1-3 days in group B, and average hospital stay was 2-4 days in group A. In the group B, the drain was removed after 2-3 days, and in some patients with small defect, there was no need for putting a drain, but in group A, the drain was removed after 2-5 days, except for one patient with large supraumbilical incisional hernia, where drain was removed after 10 days. Postoperative complications like a seroma and wound infection were comparable in both groups. Conclusion Sublay mesh repair is a better technique with less incidence of seroma formation, a lower rate of postoperative compilations like infection and wound edge necrosis, no recurrence rate, and minimal mesh related-compilations.